PENGARUH KUALITAS PRODUK TERHADAP PEMBELIAN ULANG PRODUK PADA FACTORY OUTLET SLEEPEDIA PT.SAMUDERA INDUSTRI (HILON) KABUPATEN BANDUNG - Ahmad Zaelani Adnan; Yulinar Fauziah; Ramayani Yusuf (EKBIS (Ekonomi & Bisnis), 2020)
The purpose of this research is to know the influence quality of product toward repurchasing product on Factory Outlet Sleepedia PT.Samudera industry (HILON) Kabupaten Bandung. This research uses a quantitative method, while the population and sample used in this research are numbers of customers Factory Outlet Sleepedia. In determined of sample is taken according of technic non probability sampling, it is method incidental sampling which founded by Slovin method in this research, researchers determined 100 respondens. According the result of data processing, quality of product is influence toward repurchasing product with correlation value between quality of product and repurchasing product . Based on the interpretation guidance table, the value indicates a strong correlation level. Rsquare as about 0,493 or 49,3% including high category. While 50,7% influenced by other dimensions not studied in this research. The problem is many product which the factory made, be sold in base product not in ready use product. The effort has been doing for producen it has to improve the design and variety of another product.